Improving Beef Progeny Performance Through Developmental Programming - Moriel, Philipe; Palmer, Elizabeth A.; Harvey, Kelsey M.; Cooke, R. F. (Frontiers in Animal Science, 2021)
Maternal nutritional management during gestation appears to modulate fetal development and imprint offspring postnatal health and performance, via altered organ and tissue development and tissue-specific epigenetics. This review highlighted the studies demonstrating how developmental programming could be explored by beef producers to enhance offspring performance (growth, immune function, and reproduction), including altering cow body condition score (BCS) during pregnancy and maternal supplementation of protein and energy, polyunsaturated fatty acids (PUFA), trace minerals, frequency of supplementation, specific amino acids, and vitamins. However, this review also highlighted that programming effects on offspring performance reported in the literature were highly variable and depended on level, duration, timing, and type of nutrient restriction during gestation. It is suggested that maternal BCS gain during gestation, rather than BCS per se, enhances offspring preweaning growth. Opportunities for boosting offspring productive responses through maternal supplementation of protein and energy were identified more consistently for pre- vs. post-weaning phases. Maternal supplementation of specific nutrients (i.e., PUFA, trace minerals, and methionine) demonstrated potential for improving offspring performance, health and carcass characteristics during immunological challenging scenarios. Despite the growing body of evidence in recent years, the complexity of investigating developmental programming in beef cattle production is also growing and potential reasons for current research challenges are highlighted herein. These challenges include: (1) intrinsic difficulty of accurately measuring cow milk production multiple times in cow-calf systems; (2) larger focus on Bos taurus vs. Bos indicus breeds despite the predominance of Bos indicus-influenced beef breeds in tropical/subtropical environments and their specific, and sometimes opposite, physiological and performance outcomes compared to Bos taurus breeds; (3) limited focus on interaction between prenatal and postnatal management; (4) sex-specific outcomes following similar maternal nutrition during gestation; (5) greater focus on nutrient deficiency vs. excess; (6) limited implementation of immunological challenges; and (7) lack of multigeneration and longer periods of offspring evaluation. This review provides multiple evidence that such obstacles need to be overcome in order to significantly advance the scientific knowledge of developmental programming in beef cattle and promote global beef production.